THE STUDY OF ADVERBS IN WORLD LINGUISTICS: SCIENTIFIC APPROACHES AND STAGES OF DEVELOPMENT (Journal of Universal Science Research, 2025)
This article analyzes the study of adverbs in world linguistics in a historical-logical sequence. The interpretations given to versification within the framework of structural, generative and modern cognitive approaches, starting from the ancient Greek and Arabic schools of linguistics, are studied. At each stage, the views, theoretical approaches and developments of the main scientists are presented. The article serves to provide a deeper understanding of the place of parts of speech, in particular adverbs, in the history of linguistics.